2018
DOI: 10.1002/jbmr.3580
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of a GGPPS Variant Identified in Atypical Femoral Fracture Patients and Delineation of the Role of GGPPS in Bone-Relevant Cell Types

Abstract: Atypical femoral fractures (AFFs) are a rare but potentially devastating event, often but not always linked to bisphosphonate (BP) therapy. The pathogenic mechanisms underlying AFFs remain obscure, and there are no tests available that might assist in identifying those at high risk of AFF. We previously used exome sequencing to explore the genetic background of three sisters with AFFs and three additional unrelated AFF cases, all previously treated with BPs. We detected 37 rare mutations (in 34 genes) shared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 36 publications
(44 reference statements)
2
47
0
Order By: Relevance
“…One of the most interesting genes is CYP1A1 , an enzyme involved in the metabolism of drugs and xenobiotics and responsible for the hydroxylation of steroid hormones, such as estrogens (Figure B). Mutations in CYP1A1 were found in the three sisters and one unrelated patient in our study and also reported elsewhere in two patients with AFF and glucocorticoid‐induced osteoporosis . Another study identified a missense variant in the PPEF2 gene significantly associated with AFF by exon array analysis of a small cohort .…”
Section: Atypical Femoral Fracturesupporting
confidence: 89%
See 1 more Smart Citation
“…One of the most interesting genes is CYP1A1 , an enzyme involved in the metabolism of drugs and xenobiotics and responsible for the hydroxylation of steroid hormones, such as estrogens (Figure B). Mutations in CYP1A1 were found in the three sisters and one unrelated patient in our study and also reported elsewhere in two patients with AFF and glucocorticoid‐induced osteoporosis . Another study identified a missense variant in the PPEF2 gene significantly associated with AFF by exon array analysis of a small cohort .…”
Section: Atypical Femoral Fracturesupporting
confidence: 89%
“…We also performed cellular functional assays, such as RNAi knockdown of the GGPS1 gene in osteoblasts and in osteoclasts. In osteoblasts, RNAi produced a strong mineralization reduction and a reduced expression of the typical osteoblastic markers osteocalcin, osterix, and RANKL, whereas in osteoclasts, it led to an increase of the osteoclast number with a lower resorption activity …”
Section: Atypical Femoral Fracturementioning
confidence: 99%
“…In this issue of the journal, Roca‐Ayats et al present functional studies of the GGPS1 variant and further MPS detail . Expression of wild‐type and mutant GGPPS constructs in E. coli BL‐21 cells demonstrated markedly reduced enzymatic activity of mutant GGPSS (<6%) compared with wild type, with disruption of the usual GGPPS hexameric conformation.…”
mentioning
confidence: 99%
“…The three sisters share 36 other rare (minor allele frequency <0.5%) variants in 34 genes, including a variant in CYP1A1 predicted damaging and “likely pathogenic.” Rare “likely pathogenic” CYP1A1 variants have been identified in two other AFF cases . CYP1A1 belongs to the cytochrome P450 enzyme family, which affects multiple drugs.…”
mentioning
confidence: 99%
See 1 more Smart Citation